2021
DOI: 10.2169/internalmedicine.5676-20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Barrett's Epithelium Shown by Endoscopic Observations with Linked Color Imaging in Subjects with Different <i>H. pylori</i> Infection Statuses

Abstract: Objective This study was conducted to clarify the prevalence of short segment Barrett's esophagus (SSBE) using endoscopic observations with linked color imaging (LCI). In addition, the relationship between the presence of Barrett's epithelium (BE) and the status of H. pylori infection was investigated. Methods The study subjects were 3,353 individuals (2,186 men, 1,167 women; mean age 55.2±9.4 years old) whose status of H. pylori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…In this large, retrospective cohort study comprising healthy participants who underwent screening endoscopy, we found that the prevalence of USSBE at enrollment was quite high (36.4%), which is consistent with previous reports in Japan 6–11 . Importantly, we found that the incidence of EAC in USSBE was very low (0.0068%/year; nearly as low as the incidence of GC in subjects with atrophy‐free stomach [0.0059%/year]).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this large, retrospective cohort study comprising healthy participants who underwent screening endoscopy, we found that the prevalence of USSBE at enrollment was quite high (36.4%), which is consistent with previous reports in Japan 6–11 . Importantly, we found that the incidence of EAC in USSBE was very low (0.0068%/year; nearly as low as the incidence of GC in subjects with atrophy‐free stomach [0.0059%/year]).…”
Section: Discussionsupporting
confidence: 90%
“…I N THIS LARGE, retrospective cohort study comprising healthy participants who underwent screening endoscopy, we found that the prevalence of USSBE at enrollment was quite high (36.4%), which is consistent with previous reports in Japan. [6][7][8][9][10][11] Importantly, we found that the incidence of EAC in USSBE was very low (0.0068%/year; nearly as low as the incidence of GC in subjects with atrophy-free stomach [0.0059%/year]). Although this was a retrospective study, it is the first to show concrete incidence of EAC in USSBE defined by Japanese criteria, and the outcomes will greatly influence the current clinical practice, as a huge number (15-80%) of Japanese subjects undergoing EGD are being diagnosed with USSBE.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…reported that the prevalence of BE with a length of less than 1 cm was 56.2%, while that with a length of ≥ 1 cm was 26.2% when LCI was used to determine the area of BE, as the distal end of the palisade vessels was easily visualized. 42 We investigated the inter‐institutional variability in the diagnosis of BE at four different hospitals. Because of cases of over‐ and under‐diagnosis, we demonstrated that the variance was unacceptably large (17.2%–96.8%), and the diagnostic accuracy was inadequate, especially in cases with a BE length of less than 1 cm, suggesting that the minimum length of CLE should be defined in future criteria in Japan.…”
Section: Diagnosis Of Bementioning
confidence: 99%